Addressing water scarcity in urban Tanzania: household preferences, behavioural interventions, and technological adoption - Tibanywana, Julieth Julius (School of Economics, 2026)
Access to safe drinking water remains a critical challenge in developing countries. As of 2022, only 31% of the population has access to safely managed drinking water, while the rest rely on basic, unimproved, or surface water sources. This issue is particularly severe in Dar es Salaam, Tanzania's most populous economic hub, where frequent droughts, outdated infrastructure, insufficient investments, rapid urbanization, and population growth exacerbate persistent water shortages. Between 2019 and 2023, water demand in Dar es Salaam increased by 16%, while daily production declined by 11.72%. The escalating water scarcity forces households to rely on unsafe sources, raising the risk of contamination. Addressing these challenges requires improved water conservation and reliable supply systems. This thesis examines water-related issues in Dar es Salaam from a household demand perspective through three studies: (i) households' preferences and willingness to pay for reliable water supply, (ii) the impact of information campaigns on water-saving behaviours, and (iii) the adoption of water-saving technologies. Each study is presented in a separate chapter. The first study (Chapter Two) examines household preferences and willingness to pay for reliable water service using a choice experiment design, incorporating attributes such as frequency, water quality, pressure, time of service, and cost. The study reveals preference heterogeneity and employs a random parameter logit model to capture this diversity. Findings indicate a preference for high-quality, drinkable tap water with good pressure, available either in the morning, afternoon, or at night. The study suggests that policy options should focus on improving tap water quality and pressure. The second study (Chapter Three) assesses the impact of an information campaign on water- saving behaviours using a randomized control trial involving 1,600 households, split equally into treatment and control groups. The treatment group received water usage reports for six months, comparing their consumption to the neighbourhood median. The difference-in- difference analysis indicates a reduction in water consumption by 7.65% (1.49 m³) during the campaign and 8.18% (1.6 m³) to 11.18% (2.30 m³) in the five months following the intervention. The study underscores the effectiveness of information campaigns in promoting water-saving behaviours and recommends their use by local authorities. The third study (Chapter Four) investigates the adoption of water-saving technologies, focusing on greywater technology. Data from 962 households are analyzed using Poisson and logit models to identify factors influencing adoption. The analysis reveals that factors such as age, education, income, social group membership, and awareness influence the adoption of water- saving technologies. Furthermore, the study uses a choice experiment to reveal preferences and willingness to pay for greywater technologies with longer lifespans, minimal contamination, and low odour, although high costs deter adoption. Marginal willingness to pay ranges from TZS 414,511.80 (US$180.22) to TZS 573,947 (US$249.54), representing 72.72% to 100.69% of the average monthly household income. The study recommends government incentives, such as subsidies and tax reductions, as well as campaigns to address misinformation and encourage technology adoption. These studies highlight critical areas for improving water access and conservation in Dar es Salaam, emphasizing the need for reliable water services, effective information campaigns, and supportive measures for adopting water-saving technologies.